The impact of information technology infrastructure flexibility on strategic utilization of information systems / Norizan Anwar - Anwar, Norizan (2017)
The strategic benefits of computer based information systems (IS) have been well documented in the literature. In the same light, the researcher has also unveiled various factors that promote the strategic utilization of computer based IS. Among the identified factors are information technology (IT) infrastructure flexibility. However, previous studies focusing on the contribution of IT infrastructure flexibility towards strategic utilization of IS is limited in terms of scope and coverage. Defining IT infrastructure flexibility as the composite variables, namely, (1) human IT infrastructure with dimensions such as business knowledge/skills, management knowledge/skills, technical knowledge/skills, and technology knowledge/skills, (2) technical IT infrastructure with dimensions such as IT modularity, IT compatibility, IT connectivity, and IT continuity, and (3) process IT infrastructure with dimensions such as range of physical capabilities, and range of managerial capabilities, this study has developed a conceptual framework linking the relationship of IT infrastructure flexibility on the strategic utilization of IS. To further investigate the relationship between both concepts, a fully quantitative exploratory research was conducted using a questionnaire to collect the necessary data. Two sets of questionnaire were utilized, one on the strategic utilization of IS for respondents in the business development division/unit managers, and the other one on IT infrastructure flexibility was given to IT or IS division/unit managers. The questionnaires were distributed to selected Multimedia Super Corridor (MSC) status companies located within Cybercities and Cybercentres in Klang Valley, Malaysia. 249 questionnaires were used for further analysis out of 258 that were returned. The descriptive results revealed that the responses were mostly ‘sometimes high’ in overall strategic utilization of IS and ‘sometimes agree’ in overall IT infrastructure flexibility. SPSS version 22 was used to analyze research questions 1 and 2, and SmartPLS version 3 for research questions 3 to 7. The analysis of measurement of the model led to the removal of IT continuity as a construct because the value obtained did not meet the recommended cut-off value. Thus, the variable of technical IT infastructure was reduced to three dimensions. The structural model analysis indicates that human IT infrastructure and process IT infrastructure were significant predictors of the strategic utilization of IS. Moreover, the study has also proved that process IT infrastructure is a full mediator between human IT infrastructure and strategic utilization of IS and partial mediator between technical IT infrastructure and strategic utilization of IS. The study has contributed to the body of knowledge from three perspectives namely the provision of a theoretical based framework substantiated by empirical evidence, and the development of an instrument to measure strategic utilizations of IS and its corresponding determinants. The theoretical framework developed should enable IS researchers to investigate strategic IS utilization and its corresponding antecedents in diverse IS implementation settings. Additionally, the instrument can be used by IS practitioners to measure the level of strategic IS utilizations in MSC status companies and other companies in Malaysia.